Arbor, Trellis, or Pergola—What’s in Your Garden? A Mini-Dictionary of Garden Structures and Plant Forms - Gail Hansen (EDIS, 2010)
ENH1171, a 7-page fact sheet by Gail Hansen, provides definitions and information about the origins of garden structures for people, garden ornaments, structures for animals, and plant forms. Includes references. Published by the UF Department of Environmental Horticulture, August 2010.